Ayah Tangguh, Keluarga Utuh : Pola Asuh Ayah pada Keluarga Buruh Migran Perempuan di Kabupaten Banyumas - Tyas Retno Wulan; Dalhar Shodiq; Sri Wijayanti; Dyah Woro Dwi Lestari; Ariandre Tri Hapsari; Eri Wahyuningsih; Hendri Restuadhi (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2018)
Banyumas as one of the bases of Indonesian Migrant Workers (BMI), annually dispatches about 2.000 Women Migrant Workers (BMP). Parenting is then replaced by the father's role. This study aimed to identify the role of father in child care. The study used a constructivist paradigm becaouse of the consideration that is the paradigm has the ability to reveal details of a particular community culture by understanding its natural cultural arrangement by research subject’s point of view. The method used is qualitative, requiring the skill of the researcher to reveal the thick description about the daily life of the child left behind in Banyumas Regency among 10 informants as participants of this research. The research result showed that when the mother left the children to go abroad as migrant worker, the father’s role to nurture the child became important. When the early childhood, fathers had significant roles for instrumental and expressive functions. Meanwhile, while the children were teenagers and had more complex problems, the father was needed to be more communicative, assertive, and able to reflective listen to the children’s problems and feeling. Therefore, for the women migrant’s family; the tougher the father, the stronger the family. It means that the father should have the strong will, willing to harder work, and also willing to more learn about how to practice authoritative parenting.